Natural infection versus hybrid (natural and vaccination) humoral immune response to SARS-CoV-2: a comparative paired analysis - AbdelWareth, Laila; Alhousani, Farida; Abuyadek, Rowan; Donnelly, James; Leinberger-Jabari, Andrea; Atef, Shereen; Al-Rifai, Rami H. (Frontiers in Immunology, 2023)
AbdelWareth et al, compared the Bters of three AnB SARS CoV-2 immunoglobulin (AnB-N, AnB-S and ACE2-RBD blocking Abs) among a group of naturally infected seroposiBve male parBcipants before and aXer vaccinaBon with last vaccine dose administered within ≤ 60 days or > 60 days.• More than 2-fold significant increase in all immunoglobulin Bters aXer vaccinaBon.• All immunoglobulin concentraBons (Bters) where higher in the first 60 days aXer vaccinaBons in parBcipants with hybrid immunity. • Previous SARS CoV-2 infecBon alone doesn't elicit sufficiently protecBve immune response.